Utilization of Hydrilla Verticillate in the Production of Organic Fertilizer and Horticultural Plant Cultivation in Sungai Ular Village - Secanggang, Langkat Regency, North Sumatera - Anggia Sari, Yasmine; Herlina, Netti; Nurfahasdi, Meutia; Ritonga, Aulia Rahma; Pelawi, Jesica Vina; Lingga, Dilo Andrian; Sitanggang, Trie Nova Marito; Amanda, Shakina; Silaen, Yerica Magdalena (Talenta Publisher, 2023)
The scarcity of fertilizers in Indonesia makes it difficult for farmers to find alternative fertilizers, the causes are subsidized fertilizers which are difficult to obtain, and the high cost of non-subsidized fertilizers making it burdensome for farmers. Most of the community professionals in Sungai Ular Village are farmers and the lack of availability of fertilizers and the heavy economic value of inorganic fertilizers. Based on the potential of Sungai Ular Village, Secanggang District, the raw materials for making organic fertilizer can utilize Hydrilla verticillata plants, livestock faeces and rice straw. The organic fertilizer produced can be used for traditional cultivation. The results of this community service activity, in addition to ready-to-use organic fertilizers, are horticultural crops such as kale, spinach, curly red chillies, tomatoes, basil, etc. The resulting horticultural crops are expected to increase partner agricultural yields which can increase income and support the entrepreneurial spirit of partners in optimally utilizing village potential. Community Service Activities can empower the community to realise independence and prosperity and maintain environmental sustainability by reducing the use of inorganic fertilizers (chemical fertilizers) by optimally utilizing the potential of Sungai Ular Village, Secanggang District, Langkat Regency.